Pembuatan biodiesel biji kepuh (Sterculia Foetida L.) dengan proses alkoholisis dengan katalisator buangan proses perengkahan minyak bumi pertamina unit II Palembang - Kiagus Ahmad Roni (Balai Riset dan Standardisasi Industri Palembang, 2012)
Kepuh (Sterculia foetida L.) seed oil is not utilized yet. Therefore, it should beprocessed to produce valuable product. One of the possible methods is alcoholysis with wasted solid catalyst obtained from Pertamina Unit II located in Palembang, as catalyst. With this process some benefits might be obtained from these wastes. The alkoholysis of kepuh seed oil with etanol and reactivated used solid catalyst at higher pressure was accomplished in an autoclave provided with manometer, thermometer, sampling device, heater, and mixer. The experiment was started by filling the autoclave with kepuh seed oil, alcohol, and the catalyst, then the heater and the mixer were switched on. Samples were taken out at 10 minutes intervals, and after being separated, the bottom layer was analyzed in order to determine its glycerol content using acetin method. By raising the temperature, catalyst concentration, rate of mixing, and ethanol-oil ratio, the glyceride conversion increased. From the value of k